1982
DOI: 10.1207/s15327752jpa4601_15
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability, Validity, and Utility of Three Data Modes in Assessing Marital Relationships

Abstract: Data from individual interviews, four questionnaires, and two analogue situations for 12 married couples were examined by six clinical judges and evaluated with regard to various aspects of interpersonal functioning. Orders of presentation were counterbalanced in a Latin square design. Ratings were made after each kind of data had been reviewed, after a case conference, and following discussion leading to consensus. Reliabilities were computed for the sets of variables and for each data mode. The convergent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Haynes et al (1981) developed joint and separate interview schedules which showed satisfactory validities in a mul timethod criterion study. In a careful multi method study, Boals et al (1982) compared interview, self-report, and analogue data modes, and found modest superiority for the interview. In a careful multi method study, Boals et al (1982) compared interview, self-report, and analogue data modes, and found modest superiority for the interview.…”
Section: Feelingsmentioning
confidence: 99%
“…Haynes et al (1981) developed joint and separate interview schedules which showed satisfactory validities in a mul timethod criterion study. In a careful multi method study, Boals et al (1982) compared interview, self-report, and analogue data modes, and found modest superiority for the interview. In a careful multi method study, Boals et al (1982) compared interview, self-report, and analogue data modes, and found modest superiority for the interview.…”
Section: Feelingsmentioning
confidence: 99%